2022
DOI: 10.1111/csp2.12847
|View full text |Cite
|
Sign up to set email alerts
|

Predator–prey co‐occurrence in harvest blocks: Implications for caribou and forestry

Abstract: Forest harvesting alters habitat, impacts wildlife, and disrupts ecosystem function. Across the boreal forest of Canada, forest harvesting affects ungulate prey species and their predators, with cascading impacts on other species, including threatened woodland caribou. We used camera and vegetation data and occupancy modeling to investigate what characteristics in and around forestry harvest blocks influenced the occupancy and co‐occurrence of primary prey (elk, moose, mule deer, white‐tailed deer) and predato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…Caribou are exposed to increased predation risk in areas where they overlap with ungulates and shared predators (Latham et al, 2011; Mumma et al, 2018; Whittington et al, 2011), specifically during the summer (Seip, 1992; Serrouya et al, 2011; Wittmer et al, 2005) and fall migration periods (Blagdon & Johnson, 2021). Recent research in our study area found an increased probability of bear occupancy in harvest blocks that were occupied by deer, suggesting that harvest blocks may directly influence predator–prey dynamics (McKay & Finnegan, 2022). The seasonal differences in occurrence we observed in this study could indicate seasonal differences in the spatial overlap of ungulates, caribou, and predators in areas with harvest blocks, with an associated increased caribou predation risk during the summer.…”
Section: Discussionmentioning
confidence: 72%
“…Caribou are exposed to increased predation risk in areas where they overlap with ungulates and shared predators (Latham et al, 2011; Mumma et al, 2018; Whittington et al, 2011), specifically during the summer (Seip, 1992; Serrouya et al, 2011; Wittmer et al, 2005) and fall migration periods (Blagdon & Johnson, 2021). Recent research in our study area found an increased probability of bear occupancy in harvest blocks that were occupied by deer, suggesting that harvest blocks may directly influence predator–prey dynamics (McKay & Finnegan, 2022). The seasonal differences in occurrence we observed in this study could indicate seasonal differences in the spatial overlap of ungulates, caribou, and predators in areas with harvest blocks, with an associated increased caribou predation risk during the summer.…”
Section: Discussionmentioning
confidence: 72%
“…During winter, as previously mentioned, pipelines likely offer less shelter, cover, and forage available above the snowpack than seismic lines, which is likely driving winter moose selection for pipelines only when other linear features are not available to them. At the fine scale, we found that moose were indifferent to pipelines regardless of the surrounding habitat or underlying soil wetness but that there were differences among individuals, and therefore, like seismic lines and harvest blocks, moose use of pipelines is most likely linked to finer scale characteristics like vegetation composition, lateral cover, and the presence of game trails (McKay & Finnegan, 2023; Tattersall et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
“…During summer, the width of pipelines combined with ongoing vegetation management may result in pipelines having similar thermal cover, but less forage availability than harvest blocks and wildfires, making pipelines less attractive to moose when harvest blocks and wildfires are available. Moose use of harvest blocks and pipelines during summer is linked to the availability of shrubs and lateral cover (McKay & Finnegan, 2023; Tattersall et al, 2023); pipelines are periodically cleared to maintain line‐of‐sight (Alberta Energy Regulator, 2016; MacDonald et al, 2020), while with the exception of mechanical or chemical stand tending a few years after planting, harvest blocks are left to regenerate. Therefore, harvest blocks and areas that are naturally regenerating after wildfires are likely more attractive sources of shrub and sapling moose forage than maintained pipelines with graminoids and clover less preferred by moose (MacDonald et al, 2020; McKay & Finnegan, 2023; Tattersall et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations